2002
DOI: 10.1055/s-2002-33568
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Endoscopy: Influence of Data Compression, Bandwidth and Simulated Impairments on the Usability of Real-Time Digital Video Endoscopy Transmissions for Medical Diagnoses

Abstract: rtDVT using MPEG2 [4 : 2 : 2] compression and a bandwidth of 40 Mb/s did not effectively differ from the original video images in routine tele-endoscopy. The qualitative requirements in diagnostic video endoscopy, however, are obviously much higher than previously assumed, since experienced endoscopists detected a loss of image quality and a reduction in diagnostic usability with any reduction in the technical specification. Modern methods of data compression, broadband networks and a network protocol with goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Moreover, stored video images can be readily analyzed on a personal computer. An MPEG-2 image with more than 8 Mbps enables analysis of converted motion pictures with quality equivalent to the original images [24], providing more accurate diagnoses than videotape images [25,26]. A frame rate of more than 24 fps, which is usually required for medical analyses, can also be achieved [22,27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stored video images can be readily analyzed on a personal computer. An MPEG-2 image with more than 8 Mbps enables analysis of converted motion pictures with quality equivalent to the original images [24], providing more accurate diagnoses than videotape images [25,26]. A frame rate of more than 24 fps, which is usually required for medical analyses, can also be achieved [22,27].…”
Section: Discussionmentioning
confidence: 99%
“…Flexible endoscopy for gastrointestinal examinations is a candidate because new procedures are frequently introduced in this field, and moving images also are routinely available in clinics and quite useful for the development of therapeutic skills. Many people in this field are struggling to obtain better images on narrowband networks using compression protocols [8,12,16]. Teleproctoring of open surgery is another likely application if a camera system like the one reported by Rafiq et al [13] is established to obtain good surgical pictures.…”
Section: Discussionmentioning
confidence: 99%
“…2 A study that evaluated four codecs (MJPEG, MPEG-1, MPEG-2 [4:2:0], MPEG-2 [4:2:2]) with 40 endoscopic sequences using overall image quality and usability for diagnosis found that only sequences compressed with MPEG-2 [4:2:2] at 40 Mbps were indistinguishable from the uncompressed sequence, and in addition MPEG-2 [4:2:0] at or above 8 Mbps and MJPEG at 15 Mb/s were "more or less acceptable usability for diagnosis". 3 Another study that examined the effect of four codecs (M-JPEG2000, MPEG-2, MPEG-4, H.264) on 4 bronchoscopy sequences with 256 x 256 resolution using a modified Stimulus Comparison Adjectival Categorical Judgement (SCACJ) protocol found that H.264 had the best overall quality and sequences could be compressed up to 1.34 Mbps (for dynamic video) and 0.84 Mbps (for static video) without any loss in perceived quality. 4 In this study, we assess the quality of full HD resolution laparoscopic video compressed with H.264/AVC optimized for low latency using a subjective evaluation study and state-of-the-art objective measures.…”
Section: Introductionmentioning
confidence: 99%